Recruitment Through Social Computing: A Review - Bose, Indranil; Bandyopadhyay, Indrajit (Prabandhan: Indian Journal of Management, 2010)
Since 1990s, the internet has been growingly empowered with different innovative tools and applications that made the world smaller, closer by bringing people, ideas and information together. From simple mail to complex online content management tools, collaboration tools have evolved continuously. Several hi-tech collaborating tools have emerged, leveraging on the ever evolving and improving internet and related technologies that facilitate collaboration. India is no exception to this phenomenon. According to the "Indian media forecasts" report released by Group M (June, 2008), expenditure on internet media has been growing at a phenomenal rate. This report revealed that during 2006, total expenditure on internet media in India was Rs. 204 crore (70% above previous year), which increased to Rs. 390 crore (91% higher than 2006) in 2007. As in 2008, this amount rose to Rs.624 crore (60% higher than 2007). Internet usage in India continues to grow at a slow but steady pace, both in breadth and depth, with the overall internet-using population in urban India reaching 30.32 million - a growth of 28% from April 2006 to April 2007 - according to the "India Online 2007″ study from Juxt Consult. Of the 30.32 million urban internet users, 25.17 million (83%) log on at least once to twice a week; the balance of 5.15 million (17%) are occasional users, according to the study. The penetration of the internet among urban Indians stands at 9% now, assuming the total urban population at 336 million, Juxt Consult said.